Utilizing Tiktok Application in Learning English for EFL University Students in Indonesia - Nur Aisyiah, Vemmy Maidita; Erizar, Erizar (Institut Agama Islam Negeri (IAIN) Curup, 2023)
In the current digital era, of course, learning also follows developments by using digital media. Currently, social media is one of the innovations that are widely used as learning media. It is hoped that the TikTok application can help students and lecturers create innovative and interactive English learning media. Therefore, this article aims to find out how to use the TikTok application as a medium for learning English in the digital era. This article uses the literature study method by analyzing various studies related to the use of the TikTok application as a medium for learning English. Based on the results, it shows that the TikTok application can be an English language learning medium that is easy to use, innovative, and has various advantages and benefits for students and teachers, such as increasing interest in learning and motivating students to be creative; interactive communication occurs between students and lecturers; and videos can be watched repeatedly with interesting visuals.